RANCANG BANGUN FAN UNTUK ELECTRIC DUCTED FAN (EDF) DAN ANALISIS PERFORMANYA - Buyung Junaidin (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
In aviation, electric propulsion has long been applied, one of which is the electric ducted fan (EDF). In Indonesia, initially, EDF was mostly used for the propulsion of aeromodelling aircraft for hobby purposes. LAPAN initiated the use of EDF as a drone propulsion which flown since 2013. In addition, EDF is also used in the Indonesian Rocket and Rocket Payload Competition (KOMURINDO). KOMURINDO is an annual competition for the design of rocket payloads and Electric Ducted Fan (EDF) rockets at the university level which has been held by LAPAN since 2009. In the EDF rocket competition, EDF is a secondary part of the competition because it is not required to design and build so the participants prefer products ready to use all of which come from abroad. This limits the participants in designing the EDF rocket because, in the design, the EDF specifications must be following the initial design requirements specified. Therefore, this research needs to be carried out as a first step in understanding the design process for the development of EDF. The fan is the main part of the rotating EDF or also called the rotor. Fan plays a vital role in generating thrust through accelerating airflow, so it is necessary to design to produce a fan that suits your needs. The design method used in this research is a combination of the thrust equation for the rotor and the blade element theory. The CFD method is used to analyze the performance of the designed fan which is compared with the experimental test results with the EDF test bed. The results of the design obtained that the EDF fan geometry which produces a thrust based on CFD analysis is much smaller than an initial estimate using the analytical method, it is necessary to carry out an optimization process in the process of determining the fan geometry with a better method so that the resulting thrust is following the initial estimate. The results of the EDF test show that the thrust produced by the EDF is smaller than the results of the CFD analysis, this can be due to the less optimal distance between the fan tip and the duct wall on the EDF being tested due to manufacturing results, causing the appearance of a tip vortex which reduces fan performance. In addition, the flow resistance of the duct surface is not smooth due to the manufacturing process. The CFD method can be the first step to determine the performance of the fan or EDF before proceeding to the prototype testing process because the CFD results are close to the test results.